A Short Note on Updating the Grilli and Yang Commodity Price Index - Pfaffenzeller, Stephan (World Bank, 2012)
The Grilli and Yang commodity price index is one of the most widely used commodity price series in the applied economics literature. This note provides some practical advice on updating this data series by listing the base period index values, identifying relevant data sources, and describing a method for computing subindex weights.